Taking, drawing, and using a family tree - Hanson Pierce, Heather (Henry Stewart Talks, 2021)
The reasons for taking a family history, Family tree vs. pedigree, Principles of drawing a family tree, Psychosocial aspects of taking a family tree, Gathering information of a three-generation family tree, The significance of the information from a family tree and implications for the family